The Influence of Training and Career Development on Employee Performance at PT Tugu Pratama Indonesia - Destiana Utarindasari; Destiana Kumala (International Journal of Sharia Business Management, 2023)
The purpose of this study was to determine and analyze the effect of training X1 and career development X2 on employee performance at PT Tugu Pratama Indonesia. This research is a type of explanatory research, namely research that looks at the influence between variables. The population in this study were all employees of PT Tugu Pratama Indonesia. Data collection methods in this study were questionnaires and documentation studies. The data analysis method uses descriptive and quantitative methods, namely the Multiple Linear Regression Analysis which is used to measure the effect of training and career development on employee performance at PT Tugu Pratama Indonesia. The results of the analysis show that training does not have a positive effect on employee performance and career development has a positive effect on employee performance. Based on the t-test training X1 does not have a positive and significant effect on employee performance, but career development X2 has a positive and significant effect on employee performance. Training and career development are the dominant variables affecting employee performance at PT Tugu Pratama Indonesia. Based on the F test, the F-count results are greater than the F-table (66.47>3.05) training and career development simultaneously affect employee performance at PT Tugu Pratama Indonesia